New species of the coelotine spider genus Lineacoelotes (Araneae: Agelenidae) from China - Li, Bing; Chen, Haifeng; Wu, Zhiyan; Li, Shuqiang (Zootaxa, 2019)
Four new species of Lineacoelotes Xu, Li & Wang, 2008 are described from morphological features: L. lifengyuanae sp. n. (male and female) from Chongqing Municipality, and L. tiantaiensis sp. n. (female), L. zhongbaensis sp. n. (male and female), and L. ziboensis sp. n. (male and female) from Shaanxi Province, China.